State-of-the-Art Advances in Enantioselective Transition-Metal-Mediated Reactions of Silacyclobutanes - Huang, Wei-Sheng; Wang, Qing; Yang, Hua; Xu, Li-Wen (Synthesis, 2022)
Studies on the enantioselective transformation of silacyclobutanes (SCBs) have become an emerging topic in the recent decade, due to the feature of high ring strain, and manageable Si–C bond cleavage and formation. This short review summarizes the remarkable achievements in the asymmetric transition-metal-mediated reaction of silacyclobutanes and benzosilacyclobutanes, resulting in carbon- or silicon-stereogenic organosilanes with functional substituents. 1 Introduction2 Asymmetric Transition-Metal-Catalyzed Ring Expansion Reaction3 Asymmetric Transition-Metal-Catalyzed Ring-Opening Reaction4 Conclusion and Outlook
Keywords: silacyclobutanes; benzosilacyclobutenes; transition metal; silicon–carbon cleavage and formation; silicon-stereogenic; organosilicon; ring-opening; ring expansion